Los centros de información para la supervivencia: fundamentos, proyectos innovadores y rentabilidad política - Martín Vega, Arturo (Revista General de Información y Documentación, 2006)
The complete development of the current society depends not only on scientific and technological advances but also on the standard of living. Current means of transport allow us to move so quickly and easily that cultural barriers have become increasingly blurred. People move ndividually, not collectively, in search of better life conditions. Mass communication must provide information for people in adverse situations. Governments need to create centres of survival information for those individuals who, in their environment or outside of it, lack the minimum resources to live with dignity. These centres are essential to improve coexistence. The organization is simple, but a general policy to regulate these centres would be required. This article will explain the fundamentals for the creation of this service and present the project which is underway in the Heliopolis favela (São Paulo, Brazil). The benefits which this type of service can have for both developed and underdeveloped countries in terms of improving coexistence will be pointed out.
Keywords: Survival human services; Information resources